The Effect of Coke Yield on The Performance of Regenerator 15-R-103/104 in The Residue Catalytic Unit (RCU) at PT Kilang Pertamina International RU VI Balongan - Nurkhopipah, Siti; Asminah, Ninin; Farhan, Farhan (Gema Wiralodra, 2025)
Regenerator 15-R-103/104 in the Residue Catalytic Unit (RCU) at PT Kilang Pertamina Internasional RU VI Balongan plays an important role in the Residue Catalytic Cracking (RCC) process by burning coke on the surface of the spent catalyst to restore catalyst activity and provide heat for the endothermic reaction. This study analyzes the effect of coke yield on regenerator performance using mass balance, heat balance, and thermal efficiency calculations based on Universal Petroleum Products (UOP) standards, with daily operational data for the period 1–28 January 2025. The results show that the total mass input of coke and combustion air is balanced with the flue gas output, indicating an efficient combustion process. The heat balance reveals a balanced energy distribution between heat carried by the flue gas, absorbed by the catalyst cooler, and lost due to radiation. The regenerator efficiency for each week was obtained at 57.98%, 58.07%, 56.13%, and 58.93%, with an average of 58%. The increase in coke yield was generally followed by an increase in the corrected heat of combustion, indicating a positive relationship between the amount of coke formed and the heat energy produced. These findings provide an important basis for optimizing regenerator performance in RCC systems.